Seroprevalence of Ebola virus infection in Bombali District, Sierra Leone - Mafopa, Nadege Goumkwa; Russo, Gianluca; Wadoum, Raoul Emeric Guetiya; Iwerima, Emmanuel; Batwala, Vincent; Giovanetti, Marta; Minutolo, Antonella; Turay, Patrick; Turay, Thomas B.; Kargbo, Brima; Amicosante, Massimo; Mattei, Maurizio; et al. (Journal of public health in Africa, 2017)
A serosurvey of anti-Ebola Zaire virus nucleoprotein IgG prevalence was carried out among Ebola virus disease survivors and their Community Contacts in Bombali District, Sierra Leone. Our data suggest that the specie of Ebola virus (Zaire) responsible of the 2013-2016 epidemic in West Africa may cause mild or asymptomatic infection in a proportion of cases, possibly due to an efficient immune response. December 2015. Retrospective serologic data3 suggest that EBOV might have been in circulation in Sierra Leone since 2006. The role of antibody responses in viral clearance and protection against Ebola Virus (EBOV) in humans is not fully understood. Among EVD survivors, antibodies appear as early as day-5 after symptom onset, peak 2 weeks after recovery, then decline slowly over several years.4-7 In patients with fatal outcome, antibody titers are low or absent.8 The presence of detectable anti-EBOV antibodies in asymptomatic individuals suggests exposure and a putative role of antibody response in the control of EVD and provides information on EBOV seroprevalence in at risk populations. 9 Monitoring anti-EBOV antibodies in EVD-community contacts (CCs) of index cases is crucial for assessing immune protection against EBOV. Due to the large number of infected HCWs, evaluation of anti-Ebola antibodies in this group is a useful tool for measuring the risk of occupational exposure to EBOV. The aim of the study was to assess the extent of asymptomatic or mild cases of EBOV infection among the CCs of laboratory confirmed EVD cases (survivors or deceased) and in HCWs from health facilities not involved in the management of EVD cases.
Keywords: Ebola virus infection; Sierra Leone; Seroprevalence